2015
DOI: 10.1186/s40425-015-0097-6
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab ameliorates suppressive phenotypes of myeloid antigen presenting cells in head and neck cancer patients

Abstract: BackgroundMyeloid-derived suppressor cells (MDSC) and M2 monocytes/macrophages are two types of suppressive myeloid antigen presenting cells that have been shown to promote tumor progression and correlate with poor prognosis in cancer patients. Tumor antigen specific monoclonal antibodies (mAb) have emerged as important agents for cancer therapy. In addition to the direct inhibition of tumor growth, the Fc portions of the therapeutic mAbs, such as the IgG1 portion of the anti-epidermal growth factor receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…The role of anti-EGFR mAbs on myeloid cells in the context of HNSCC is yet undetermined, some studies suggest that panitumumab may mediate ADCC through CD32/FcγRIIa expressed by monocytes (13). Furthermore, recent data suggest that cetuximab may ameliorate suppressive phenotypes of myeloid cells in HNSCC patients (28). However, no significant difference in activation markers on isolated CD14 + monocytes was noted between cetuximab and panitumumab.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of anti-EGFR mAbs on myeloid cells in the context of HNSCC is yet undetermined, some studies suggest that panitumumab may mediate ADCC through CD32/FcγRIIa expressed by monocytes (13). Furthermore, recent data suggest that cetuximab may ameliorate suppressive phenotypes of myeloid cells in HNSCC patients (28). However, no significant difference in activation markers on isolated CD14 + monocytes was noted between cetuximab and panitumumab.…”
Section: Discussionmentioning
confidence: 99%
“…In HNSCC patient samples, we noted increased EGFR-positive CTL following treatment with cetuximab, this was not seen in patients treated with panitumumab. Given that recently published data indicated that mDC phenotype and myeloid-derived suppressor cells induction correlated with clinical response to cetuximab, a potential mechanism of myeloid-DC priming may underlie this enhancement of EGFR-specific T cell expansion (28). …”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Tim-3 expression, in response to certain cytokines, has been reported to be induced by activation of the PI3K pathway. 26 We previously showed that pS6 is decreased in TIL after PD-1 stimulation, 30 potentially linking PD-1 to the PI3K-Akt-mTOR pathway. Since TCR/CD28 co-stimulation leads to PI3K/Akt activation, and PD-1 ligation causes inhibition of TCR proximal signaling through SHP-2 27 , leading to decreased PI3K activity, we hypothesized that Tim-3 upregulation after PD-1 blockade might be caused by increased PI3K activity due to de-repression by PD-1 blockade.…”
Section: Tim-3 Upregulation Upon Pd-1 Blockade Requires Activation Ofmentioning
confidence: 99%
“…Immunosuppression in the HNSCC microenvironment is mediated by regulatory T cells (Treg), myeloid derived suppressor cells (MDSC) [3][4][5][6] and dysfunctional or exhausted antitumor effector T cells. During chronic viral infection, exhausted T cells undergo an altered transcriptional program with upregulation of several transcription factors, including Eomes, Blimp-1 and BATF, and downregulation of T-bet.…”
Section: Introductionmentioning
confidence: 99%